Optimization of parameters for deposition of In2S3 films by spray pyrolysis using Taguchi method. (23rd March 2016) - Elfarrass, S.; Hartiti, B.; Ridah, A.; Thevenin, P.
ABSTRACT: The aim of this research is to investigate the influence of the experimental conditions on the structural, morphological and optical properties of Indium Sulfide thin films deposition according to the Taguchi analysis method. The films are deposited on a glass substrate by spray pyrolysis a deposition method which is dependent on the concentrations of the precursor (indium and sulfide), the substrate temperature and the duration of the process. These four parameters are the key factors to be optimized in our study in conjunction with the morphological and optical properties of the films thanks to the Taguchi analysis, using a L9 Orthogonal array.